2020
DOI: 10.12998/wjcc.v8.i19.4320
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mTOR gene polymorphisms and gene-tea interaction on susceptibility to tuberculosis

Abstract: BACKGROUND mTOR gene is a key component of the PI3K/Akt/mTOR signaling pathway, and its dysregulation is associated with various diseases. Several studies have demonstrated that tea drinking is a protective factor against tuberculosis (TB). This study was designed to explore five single nucleotide polymorphisms (SNPs) of mTOR in the Han population of China to determine how their interactions with tea drinking affect susceptibility to TB. AIM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Furthermore, according to the results of the marginal structural linear odds models, we discovered a negative interaction between rs7568402 of PD-1 genes and tea drinking, which indicated that tea drinking, consistent with our prior studies [ 5 , 28 ], was a protective factor in TB infection. Moreover, black tea, oolong and green tea were all confirmed to be inversely associated with TB and significant dose–response relationship was discovered [ 5 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, according to the results of the marginal structural linear odds models, we discovered a negative interaction between rs7568402 of PD-1 genes and tea drinking, which indicated that tea drinking, consistent with our prior studies [ 5 , 28 ], was a protective factor in TB infection. Moreover, black tea, oolong and green tea were all confirmed to be inversely associated with TB and significant dose–response relationship was discovered [ 5 ].…”
Section: Discussionsupporting
confidence: 90%
“…The study participants included 503 TB patients and 494 controls. The distributions of demographic characteristics and associated risk factors between the TB patient group and the control group have been reported in our previous study [ 28 ]. The two groups exhibited no statistical difference ( P > 0.05) in terms of sex, age, marital status, educational background and alcohol drinking, while differences in BMI, history of BCG vaccination, smoking status and tea drinking were statistically significant ( P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We investigated the association of three MASP2 SNPs and TB susceptibility using a case–control study. There was a statistical difference in BMI, history of BCG vaccination, smoking and tea drinking between the case group and the control group (P < 0.05), but no statistical difference was found in gender, age, marital status, educational background and alcohol consumption (P > 0.05), the data was cited from reference 28 .…”
Section: Resultsmentioning
confidence: 93%
“…To exclude possible confounding risk factors, the occurrence of TB was used as the dependent variable, the rs12142107, rs12711521, and rs7548659 of MASP2 genes were used as the independent variables, and the sex, age, marital status, educational background, BMI, smoking status, alcohol drinking, and tea drinking were used as the covariates, and multivariate unconditional logistic regression analysis conducted. The additive interaction of marginal structural linear odds models were used for point estimation and interval estimation of the relative excess risk of interaction (RERI) to analyze the gene-environment interaction 28 . RERI > 0 suggests positive interactions.…”
Section: Methodsmentioning
confidence: 99%